IMPLEMENTATION OF ANTI-CORRUPTION EDUCATION VALUES IN THE SUBJECTS OF AQIDAH AKHLAK IN MADRASAH ALIYAH NEGERI 3 MEDAN - Saima Sakilah Dalimunthe (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This research discusses one chronic problem of the nation which iscurrently in urgent need of an effort to solve it, namely the act ofcorruption. Efforts made in suppressing future acts of corruption arethrough the application of anti-corruption education values. Education isplaced in a strategic position. Application of anti-corruption Educationvalues through learning is the inculcation of the values of human life as moral and moral beings, but in fact there are many cases that are very contrary to good morals and morals. Like many corruptors who comefrom the basis of a strong religion. This phenomenon is the problem inthis study, how the anticorruption education values are integrated in thesubjects of Aqidah Akhlak in Madrasah Aliyah Negeri 3 Medan, how arethey implemented in learning, what are the obstacles encountered andsuggestions from the implementation. The purpose of this study is to findout what the values of anti-corruption education contained in theAqeedah Moral subjects in Madrasah Aliyah Negeri 3 Medan, to find outthe implementation of the values of anti-corruption education in theAqidah Morals in the Aliyah Negeri 3 Medan Madrasah and to determinethe constraints and solution to the implementation of anti-corruptioneducation values in the subjects of Aqidah Akhlak in Madrasah AliyahNegeri 3 Medan. This research is a qualitative study by taking thebackground of Madrasah Aliyah Negeri 3 Medan. The subjects of thestudy were the school principal, deputy head, teachers of the AqidahMorals and student trainees and. Data collection is done by using interviews, observation and documentation. Checking the validity of the data is done using triangulation of sources and methods. Data analysis iscarried out by giving meaning to the data that was collected, from whichconclusions are drawn by describing descriptively. The results showed:the values of anti-corruption education contained in the subjects ofAqidah Akhlak in Madrasah Aliyah Negeri 3 Medan are honesty, justice,responsibility and trustworthiness, hard work, istikomah and sincere. Theimplementation of anti-corruption education values in learning is done bysuppressing these values when explaining, providing insights related toanti-corruption material to students on the sidelines of learning materialas an introduction to the hidden curriculum (hidden curriculum), so that it includes exemplary values, attitudes and habituation. The obstacle in this research is how to discipline and understand students as a whole about the learning being taught and the solution is that teachers must understand it repeatedly and repeatedly. And make students who are stubborn in the class aware, because they are dragging the subject.